Fibrillar Type I Collagen Matrices Enhance Metastasis/Invasion of Ovarian Epithelial Cancer Via β1 Integrin and PTEN Signals. Issue 8 (1st October 2012) - Shen, Yufei; Shen, Rong; Ge, Lili; Zhu, Qiaoying; Li, Fengshan
Abstract : Objective: This study investigated the involvement of fibrillar collagen in remodeling extracellular matrices (ECM) and its significant impact on the metastasis/invasion of epithelial ovarian cancer cells via β1 integrin/phosphatase and tensin homolog (PTEN) signaling. Materials/Methods: Normal ovarian surface epithelium tissues (n = 13), ovarian cancer tissues (n = 28), ovarian cancer cell lines, and a 3-dimensional model of fibrillar type I collagen that mimicked pathological ECM in vivo were used in the study. We explored the specific mechanisms behind ECM remodeling and the cellular signals that affected the invasion of ovarian cancer cells. Results: The data showed that increased β1 integrin expression in ovarian cancer cells led to enhance migration/invasion of ovarian cancer cells via regulation of PTEN/protein kinase B (Akt) signal in response to fibrillar type I collagen matrices. Low PTEN activity corresponded to the following: (1) increased PTEN degradation and (2) phosphorylation of PTEN. Decreased protein phosphatase 2A activity was detected in ovarian cancer. Protein phosphatase 2A might play a role in enhancing the progression of ovarian cancer through regulating PTEN/Akt signal. Conclusion: These findings indicate that fibrillar type I collagen, by modulating integrin-PTEN/PI3K/Akt signaling pathway in remodeling ECM, is very important in affecting the invasion of aggressive ovarian cancer cells. Moreover, these data provide direct evidence for pathological ECM remodeling and cell signaling networks involved in the invasion of ovarian cancer cells.